LADY DIANAâ€™S CONSTRUCTED REPRESENTATION OF PSYCHOLOGICAL DISORDER IN THE DOCUMENTARY â€œDIANA: IN HER OWN WORDSâ€ - Aurellia, Anastasia (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTDocumentaries represent facts by wrapping them into structured films. However, the figures indocumentaries are still constructed by the directors. Lady Diana as the main figure of thedocumentary in â€œDiana: In Her Own Wordsâ€ was analyzed in terms of three-dimensional aspects:physically, socially, and psychologically. The methods that were used in collecting the data weredocumentation and observation methods. The theories that were used in this study were Egriâ€™stridimensional theory and American Psychiatric Associationâ€™s theory of psychological disorder.Several findings that were found from the analysis are; Lady Dianaâ€™s physical and sociologicaldimensions that were linked to her psychologically; and her psychological disorders; bulimianervosa and borderline personality disorder (BPD).Keywords: Lady Diana, Constructed Representation, Psychological Disorder,DocumentaryABSTRAKDokumenter menyajikan fakta dengan menggabungkannya sebagai satu kesatuan film.Meskipun demikian, figur dalam dokumenter terkonstruksi oleh sang direktur. LadyDiana sebagai figur utama dalam dokumenter Diana: In Her Own Words dianalisis darisegi aspek tiga dimensi: fisik, sosial, dan psikologi. Metode yang digunakan dalammengumpulkan data adalah dokumentasi dan observasi. Teori-teori yang digunakan didalam studi ini didapat dari teori tridimensional oleh Egri dan teori kelainan psikologisoleh American Psychiatric Association. Beberapa temuan yang ditemukan dari Analisadata adalah dimensi fisik dan sosial dari Lady Diana yang berhubungan dengannyasecara psikologis; dan kelainan psikologisnya, yaitu bulimia nervosa dan gangguankepribadian ambang (BPD).Kata kunci: Lady Diana, Representasi Terkonstruksi, Kelainan Psikologis, Dokumenter